Development of Musi Board Teaching Media on Math Arithmetic Operation for Grade II Elementary School Student - Pratama, Dimas Wahyu; Mulyawati, Ima (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research is based on the problems that exist in math subjects, especially in multiplication, adding, and subtracting. One of the fundamental problems experienced by students is a lack of understanding of basic concepts due to the lack of understanding of students reasoning and only paying attention to what is on the blackboard and the lack of learning media used during learning. In order for their understanding and numeracy skills to increase, learning resources for the Musi Board are needed. This study aims; (1) to test the feasibility of Musi Board Media on math arithmetic operations; (2) to see students response when learning using Musi Board Media on math arithmetic operations; (3) the effectiveness of Musi Board Media on math arithmetic operations. Using the ADDIE methodology (analysis, design, development, implementation, and evaluation), this study used the Research and Development approach. The study involved 26 students from grade II of SDN dukuh 08. This media had shown the validity of the media and materials with 94% and 95%, respectively, with a very feasible category. Students’ responses also reached 96%, respectively, with a very interesting category. The results show that this Musi Board Media is feasible to use to help students learning. Therefore, the solution to overcome the problems of students to understand the basic concepts of mathematics in counting operations is to use the media during the lesson. With an N-gain value of 59.26%, the effectiveness of utilizing Musi Board medium for math arithmetic operations falls into the Moderately Effective group.